Probabilistic approach to assessing tribotechnical reliability indicators of friction units - Dykha, M.O.; Dytyniuk, V.O.; Staryi, A.L. (Problems of Tribology, 2025)
The article presents a theoretical and analytical review of the probabilistic approach to assessing the tribotechnical reliability of mechanical systems, in particular friction units. The influence of the random nature of loads and wear on the reliability of machine elements is considered. The feasibility of using distribution functions and probability density functions to describe the wear process is substantiated. Mathematical models are described in detail that allow determining the probability of element failure for given statistical characteristics of the load and permissible wear. Both constant and block load conditions are taken into account. The results of the study can be used in the design and operation of highly reliable tribotechnical systems, as well as for predicting their resource under conditions of operational uncertainty.